Transformations of halogenated organic compounds under denitrification conditions. - Bouwer, E J (1983)
Trihalomethanes, carbon tetrachloride, 1,1,1-trichloroethane, 1,2-dibromoethane, chlorinated benzenes, ethylbenzene, and naphthalene at concentrations commonly found in surface and groundwater were incubated under anoxic conditions to study their transformability in the presence of denitrifying bacteria. None of the aromatic compounds showed significant utilization relative to sterile controls at initial concentrations from 41 to 114 micrograms/liter after 11 weeks of incubation. Of the halogenated aliphatic compounds studied, transformations of carbon tetrachloride and brominated trihalomethanes were observed after 8 weeks in batch denitrification cultures. Carbon from the decomposition of carbon tetrachloride was both assimilated into cell material and mineralized to carbon dioxide. How this was possible remains unexplained, since carbon tetrachloride is transformed to CO2 by hydrolysis and not by oxidation-reduction. Chloroform was detected in bacterial cultures with carbon tetrachloride initially present, indicating that reductive dechlorination had occurred in addition to hydrolysis. The data suggest that transformations of certain halogenated aliphatic compounds are likely to occur under denitrification conditions in the environment.